Financial Governance Management for Farmers, Ranchers, and Weavers of Camplong Ii Village, Kupang Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Camplong II Village is one of the villages in Kupang Regency, NTT with uniqueness in producing weaving both from the dyeing process, and weaving to selling weave products in the market, but business development in this village is quite slow. After identifying the problem, three biggest issues can be obtained, namely the problem of people's mindset towards the potential of weaving for community welfare, inefficient and innovative production processes, and lack of knowledge of entrepreneurship and business management. The community of ranchers and weavers is the basis for the proposal of this service, with the hope that it can be the initial stage of improving the mindset, community motivation, and business management in agriculture, animal husbandry, and tie weaving. The goal to be achieved in this community partnership program is to make farmers, ranchers, and weavers of Camplong II Village aware of the importance of good financial management and animal health management so that they can meet current and future needs. Activities in this service start from designing training activities, selecting instructors, Technical Guidance financial management, and animal health, and then conducting evaluation and feedback. The methods used are direct education and public assistance. The result of this service is an increase in the knowledge and skills of farmers, ranchers, and weavers in groups. Then counseling and assistance in financial governance management and animal health management by the Community Service team that made farmers, ranchers, and weavers experience improvement.